2004
DOI: 10.1021/jm0493616
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Indole Fatty Alcohols on the Differentiation of Neural Stem Cell Derived Neurospheres

Abstract: In a search for inducers of neuronal differentiation to treat neurodegenerative diseases such as Alzheimer's disease, a series of indole fatty alcohols (IFAs) were prepared. 13c (n = 18) was able to promote the differentiation of neural stem cell derived neurospheres into neurons at a concentration of 10 nM. Analysis of the expression of the Notch pathway genes in neurospheres treated during the differentiation phase with 13c (n = 18) revealed a significant decrease in the transcription of the Notch 4 receptor. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
35
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 28 publications
6
35
0
Order By: Relevance
“…Indeed, AGT251 treatment partly counteracted both in vitro and in vivo stress-induced Notch pathway activation. However, in C2C12 myoblastic cells and in muscles of ALS or doxorubicin-treated animals, the repression was mostly observed on Notch1 and Notch3 but not on Notch4 as previously seen in neurons (Coowar et al, 2004). In addition, here we also provided the first evidence that regulation of the Notch receptor by tocopherol derivatives impacts the Notch target genes.…”
Section: Tocopherol and Flavanoid Activity On Muscle Via Notchsupporting
confidence: 85%
See 3 more Smart Citations
“…Indeed, AGT251 treatment partly counteracted both in vitro and in vivo stress-induced Notch pathway activation. However, in C2C12 myoblastic cells and in muscles of ALS or doxorubicin-treated animals, the repression was mostly observed on Notch1 and Notch3 but not on Notch4 as previously seen in neurons (Coowar et al, 2004). In addition, here we also provided the first evidence that regulation of the Notch receptor by tocopherol derivatives impacts the Notch target genes.…”
Section: Tocopherol and Flavanoid Activity On Muscle Via Notchsupporting
confidence: 85%
“…shown that tocopherol derivatives repressed mRNA level for Notch4 in neuronal cells (Coowar et al, 2004). Our study brings novel information on these two aspects.…”
Section: Tocopherol and Flavanoid Activity On Muscle Via Notchmentioning
confidence: 52%
See 2 more Smart Citations
“…9 Several small heterocyclic molecules have been demonstrated to be capable of inducing stem-cell proliferation and differentiation in vitro. 10,11 8-Hydroxyquinoline derivatives are important constituents in a variety of pharmaceutically important compound classes. They have become of interest as a new class of potent HIV-1 integrase inhibitors, 12 for modeling of the inhibition of retroviral integrases, 13 as protein tyrosine kinase inhibitors, 14 as protozoal and retroviral co-infections 15 and as anti-HIV-1 agents.…”
Section: Introductionmentioning
confidence: 99%